2023
DOI: 10.3390/jcm12020640
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Post-Exercise Hypotension after Different Sprint Interval Training Protocols in a Matched Sample of Younger and Older Adults

Abstract: This study assessed the post-exercise hypotension (PEH) effect in a sample of matched young and older adults after different sprint interval training (SIT) protocols. From forty-three participants enrolled in this study, twelve younger (24 ± 3 years) and 12 older (50 ± 7 years) participants, matched for the body mass index, systolic blood pressure, and VO2max-percentiles, were selected. The participants completed two SIT protocols consisting of 4 × 30 s exercise bouts interspersed by either one (SIT1) or three… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In addition, small fluctuations in arterial pressure are not easily detected in people with different levels of body fat. As a result, the tightness of the textile-based TENG can be adjusted to fit the human body, promoting sensitivity and accurately converting pulse waves into electrical signals [ 84 , 85 ]. In the future, researchers can increase the sensitivity of TENG by changing its structure and material.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In addition, small fluctuations in arterial pressure are not easily detected in people with different levels of body fat. As a result, the tightness of the textile-based TENG can be adjusted to fit the human body, promoting sensitivity and accurately converting pulse waves into electrical signals [ 84 , 85 ]. In the future, researchers can increase the sensitivity of TENG by changing its structure and material.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Another method of inducing PEH is using sprint interval training (SIT), which has shown that the length of the interval between successive sprints and the age of the subjects can affect their post-exercise response. Specifically, longer resting intervals appear to provide a stronger physiological stimulus, suggesting that resting between successive exercise may in fact produce a greater PEH [ 10 ]. However, further studies are needed to investigate the effects of other SIT protocols to determine the optimal resting protocol for maximizing the PEH effect.…”
mentioning
confidence: 99%